The Association of Depressive Symptoms and Intimate Partner Violence Against Women in Northwestern Botswana. Issue 9 (May 2021) - Barchi, Francis; Winter, Samantha C.; Dougherty, Danielle; Ramaphane, Peggie; Solomon, Phyllis L.
Although links between mental health and intimate partner violence (IPV) have been discussed extensively in the scholarly literature, little empirical data exist about these phenomena in Botswana. This study addressed this gap by examining the nature, extent, and risk factors associated with symptoms of major depressive disorders (MDD) using cross-sectional data collected in 2009-2010 in northwestern Botswana. A random sample of 469 women participated in semistructured interviews about their lives, health, and experiences with violence. Thirty-one percent of respondents were found to meet the symptom criteria for MDD. Factors associated with MDD included emotional or physical violence by an intimate partner and being in a relationship in which both partners consumed alcohol. One in five women reported a recent experience of emotional violence, while 37% of respondents reported recent physical IPV. Women who have experienced emotional or physical IPV in the last 12 months have 89% and 82% greater odds, respectively, of having symptoms of MDD ( p < .05) than women who have not recently experienced either form of violence. Women in relationships in which both partners consumed alcohol had more than twice the odds of MDD compared with women in relationships where neither partner or only one partner drank. Given the significant association of violence, alcohol, and MDD, screening for all three conditions should be part of routine care in health care settings in Botswana. Interventions to reduce IPV and alcohol consumption may help alleviate the burden of MDD in women in this setting.